2017
DOI: 10.2147/dddt.s107018
|View full text |Cite
|
Sign up to set email alerts
|

The antiulcer effect of <em>Cibotium barometz</em> leaves in rats with experimentally induced acute gastric ulcer

Abstract: Cibotium barometz is a pharmaceutical plant customarily used in traditional medicine in Malaysia for the treatment of different diseases, such as gastric ulcer. The gastroprotective effect of C. barometz leaves against ethanol-induced gastric hemorrhagic abrasions in Sprague Dawley rats has been evaluated in terms of medicinal properties. Seven groups of rats (normal control and ulcerated control groups, omeprazole 20 mg/kg, 62.5, 125, 250, and 500 mg/kg of C. barometz correspondingly) were used in antiulcer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 54 publications
3
31
0
1
Order By: Relevance
“…This outcome led us to hypothesize that the up-regulation of HSP70 protein synthesis might play an essential role in promoting the gastroprotective effect of γ-mangostin, possibly by attenuating ROS-mediated gastric oxidative stress. Similarly, numerous studies demonstrate that the upregulation of HSP70 in experimental animals protect stomach from necrotizing agents (Halabi et al 2014;Nazarbahjat et al 2016;AL-Wajeeh et al 2017). The results of the current study revealed that stomach tissue homogenates from experimental groups showed expressively reduced levels of MDA and elevated levels of SOD and CAT in retort to oxidative stress induced by absolute ethanol.…”
Section: Discussionsupporting
confidence: 69%
“…This outcome led us to hypothesize that the up-regulation of HSP70 protein synthesis might play an essential role in promoting the gastroprotective effect of γ-mangostin, possibly by attenuating ROS-mediated gastric oxidative stress. Similarly, numerous studies demonstrate that the upregulation of HSP70 in experimental animals protect stomach from necrotizing agents (Halabi et al 2014;Nazarbahjat et al 2016;AL-Wajeeh et al 2017). The results of the current study revealed that stomach tissue homogenates from experimental groups showed expressively reduced levels of MDA and elevated levels of SOD and CAT in retort to oxidative stress induced by absolute ethanol.…”
Section: Discussionsupporting
confidence: 69%
“…Cibotium barometz (L.) J. Smith is a tropical and sub-tropical plant, also known as “golden hair dog fern,” used as medicinal plant in Malaysian Peninsula and parts of China. The gastroprotective effect of the ethanolic extract from its leaves [ 53 ] and hairs [ 54 ] was evaluated against ethanol-induced stomach ulcers in Sprague Dawley rats at 62.5, 125, 250 and 500 mg/kg. The C. barometz leaves presented a dose-dependent antiulcer effect, increased antioxidant enzymes activity, such as superoxide dismutase (SOD), CAT and glutathione peroxidase (GPx) and decreased lipid peroxidation [ 53 ].…”
Section: Plant Products and Phytochemicals As Antiulcerogenic And mentioning
confidence: 99%
“…The gastroprotective effect of the ethanolic extract from its leaves [ 53 ] and hairs [ 54 ] was evaluated against ethanol-induced stomach ulcers in Sprague Dawley rats at 62.5, 125, 250 and 500 mg/kg. The C. barometz leaves presented a dose-dependent antiulcer effect, increased antioxidant enzymes activity, such as superoxide dismutase (SOD), CAT and glutathione peroxidase (GPx) and decreased lipid peroxidation [ 53 ]. On the other hand, C. barometz hairs presented a dose-dependent antiulcer effect too, free radical scavenging activities, increased pH, gastric mucus glycoprotein and antioxidant enzymes activity (SOD, CAT and GPx) and reduced MDA levels [ 54 ].…”
Section: Plant Products and Phytochemicals As Antiulcerogenic And mentioning
confidence: 99%
See 1 more Smart Citation
“…This effect was attributed to increased antioxidant activity, mucus preservation, upregulation of HSP-70, and downregulation of Bax proteins [51]. Similarly, C. barometz leaves also demonstrated a gastroprotective effect against ethanol-induced gastric ulcers in rats, an effect attributed to upregulated HSP-70 expression and downregulation of Bcl-2 protein expression [52].…”
Section: Gastroprotective Plants With Anti-apoptotic Effectsmentioning
confidence: 90%